Selection of institution of higher learning for study abroad: a Malaysian case study - Rahman, Mahbubar; Islam, Rafikul (Malaysian Institute of Management, 2016)
This study examines why international students select the International Islamic University Malaysia (IIUM) as their Higher Learning Institute (HLI) when pursuing higher education. Using a qualitative approach, with the philosophical foundation of case study method, and employing interviews to gather data, a total of 8 postgraduate international students from IIUM were purposefully selected with consideration to their different disciplines, country of origin, study levels, length of stay, and gender. The study finds the international students are well concerned about their selection of the university where they want to enrol. In relation to university selection by international students, the study specifically focuses on some factors which influence the choice of a study destination, particularly a university for higher education. The study reveals that as a HLI of Malaysia, IIUM has a good reputation among the international students although the level of positivity varies from case to case. The results are primarily beneficial to academics and researchers to understand the related issues of how the foreign students select their institution for pursuing higher studies.